Associations between time since onset of injury and participation in Dutch people with long-term spinal cord injury. Issue 12 (December 2018) - Ruijter, Leonie; Groot, Sonja; Adriaansen, Jacinthe; Smit, Christof; Post, Marcel
Abstract Study design Multicentre cross-sectional study. Objectives To describe relationships between time since injury (TSI) and participation in individuals with tetraplegia and paraplegia. Setting Community sample from the Netherlands Methods Individuals (N  = 265) aged 28–65 years, living with spinal cord injury (SCI) for ≥10 years, age at injury between 18–35 years and using a wheelchair for everyday mobility in three TSI strata: 10–19, 20–29, and ≥30 years post-injury. The Utrecht Scale for Evaluation of Rehabilitation-Participation (USER-Participation) was used, which consists of three scales: Frequency (including subscales for Productive, Leisure, and Social activities), Restrictions, and Satisfaction. Linear regression analyses were used to study the effect of TSI on participation, and to adjust for personal and lesion characteristics, for individuals with tetraplegia and paraplegia separately. Results Mean age was 48.4 years, with a mean TSI of 24 years. About 73.6% were male, 40.4% had tetraplegia and 81.9% had a motor complete injury. In individuals with tetraplegia (N  = 107), longer TSI was independently associated with lower scores on the Frequency scale (p  = 0.025) and the subscale frequency of Leisure activities (p  = 0.004). In individuals with paraplegia (N  = 158), longer TSI was independently associated with lower scores on the subscale frequency of Productive activities (p  = 0.006). TSI was not associated with participation Restrictions and Satisfaction with participation. Conclusions Longer TSI is associated with a reduced frequency of participation in individuals with long-term SCI. Interestingly, this negative association is not accompanied by a similar association in the person's experience of participation.